The Functional Imperative: The Practical Role of Christian Angelic Beliefs in the Ming and Qing Dynasties - He Sun (Religions)
The introduction of Christian angelology during the Ming and Qing dynasties was driven by strong practical needs. As intermediaries bridging the sacred and the secular, angels were endowed with crucial functions in core sacraments such as baptism and the Mass, including the purification of sins, protection, and the connection between God and humanity. Their participation in these rituals not only enhanced the sanctity of the ceremonies but also facilitated a dialogue with traditional Chinese spirits. Missionaries deliberately avoided abstract theological discussions about angels, instead emphasizing their role in accompanying and guiding believers in daily life. The concept of “guardian angels” addressed the spiritual needs of believers, while the imagery of angels in funeral rites helped reconstruct expressions of filial piety, thereby mitigating cultural conflicts between China and the West. At the same time, the localized understanding of angels among Chinese Catholics during this period focused on ritual practices and the affirmation of their own identity. The introduction of Christian angels during the Ming and Qing dynasties, with their practical dimensions, facilitated the indigenization process of Catholicism in China and provided new perspectives and pathways for interreligious and intercultural dialogue.